Horizontal Adaptable Program Lending : Assessing Suitability for Risk Management of Natural and Climate-induced Hazards in Pacific Island Countries - World Bank (Washington, DC, 2013)
The Pacific Island Countries (PICs) are highly vulnerable to natural and climate-induced hazards and this vulnerability is likely to increase over the coming decades. Climate change and natural hazards will have repercussions on coastal development, water supply, energy, agriculture, and health, among other sectors. Therefore, risk management of natural and climate-induced hazards (RMNCH), including climate adaptation, are core development issues for the PICs and the economic, social and environmental benefits of RMnCH investments are likely to far outweigh their costs. The World Bank is currently considering scaling up its engagement in RMNCH activities in the PICs. Specifically, the intention is to develop a business plan to address priority RMCH issues, including both technical assistance and investment activities. However, given the large number, diversity, specific needs, relatively small size, and isolation of the PICs, providing assistance using traditional lending instruments could be a costly, administratively difficult and time-consuming exercise. Likewise, several donors have expressed interest in working on this challenge, which, given the generalized weakness in the PICs' institutional capacity, can generate an undue burden in the absence of coordinated action. Consequently, it is of utmost importance to find ways of reducing administrative and related overheads (even if the World Bank were the only donor) while still maintaining the goal of maximizing assistance, maintaining consistency, transparency, and efficiency and harmonizing initiatives of the PICs to address their RMNCH needs.